Perspectives on systematic capacity building in pharmaceutical regulation for regulators of medical products - Gwaza, Luther; Chemwolo, Andrew; Musonda, Mario; Kuwana, Rutendo; Dube, Admire (Frontiers in Medicine, 2024)
Having a robust, integrated regulatory system is important for ensuring the availability of safe and efficacious medical products of good quality and for protecting public health. However, less than 30% of countries globally have reached the required regulatory maturity level three, with low- and middle-income countries facing challenges in attracting and retaining qualified staff. World Health Organization (WHO) advocates for systematic workforce development, including competency-based education, to address these gaps. We provide perspectives on a systematic approach to capacity building of medicine regulators based on the experience and lessons learnt in developing and piloting the WHO global competency framework for medicine regulators through three scenarios. A systematic approach to capacity building, such as the human performance technology model, can be used to implement the WHO competency framework as part of organizational performance improvement while ensuring that initiatives are well-defined, targeted, and aligned with organizational goals. The competency framework can be used in different contexts, such as improving organization performance for individual regulatory authorities, strengthening regional collaborations, harmonization and reliance on medical products assessment and joint good manufacturing practices inspections of pharmaceutical manufacturers, and developing learning programs for medicine regulators. A competency-based learning approach for regulatory professionals ensures the transfer of learning to the workplace by integrating real-world practices in learning activities and assessments. Further work is required to develop and validate the assessment instruments, apply the competency framework in other contexts, expanding the learning programmes while continuously providing feedback for further refinement of the competency framework and implementation support tools.